Estudio comparativo entre bases de datos relacional y no relacional - Saltos Pérez, Luis Arturo (2022)
The DB-Engines platform represents key information about the level of popularity that exists between the two types of databases, based on the data provided it was identified that the relational database covers a large segment in the database market. This is because it is an old technology that focuses on structured storage solutions. In addition, it also shows a perspective of the different models of non-relational databases, being a technology that is in full growth, a certain degree of acceptance was observed for having a high degree of compatibility in new applications that require storing unstructured data of large information banks. In the relational database it is necessary to establish a structure in the form of a table to store the data. Where each table contains a primary key that is related to the other tables by means of a secondary key to facilitate access to the data. Non-relational databases are designed to operate in a distributed architecture that facilitates the replication of information in different storage centers, they do not use a defined related structure since they implement APIs to access information. The comparative study between relational and non-relational databases is carried out with the aim of providing information on the main characteristics, advantages and disadvantages that constitute each relational and non-relational database model, to subsequently establish a comparative table that provides information to Future investigations.